Revitalisasi Bahasa Bali Melalui Seni Pertunjukan Drama Gong - I Wayan Sugita; I Gede Tilem Pastika (Dharma Sastra: Jurnal Penelitian Bahasa dan Sastra Daerah, 2022)
This article aims to discuss the existence of the performing arts of drama gong as an educational medium to revitalize the Balinese language. As a result of the qualitative study, data collection was carried out through observation, document review, and in-depth interviews with several key informants who understand the Balinese language and culture. Data analysis was carried out by applying the theory of symbolic interactionism and semiotics. The results of the study show that the drama gong is a performing art that is loved by the Balinese people and consistently uses Balinese as its introduction so that the vitality of the Balinese language can be maintained. Drama gong has become a Balinese language education medium that can directly target young Balinese as supporters of the Balinese language. Besides teaching Balinese language patterns, drama gongs also teach Balinese sorsinggih and the social structure of Balinese society. The drama gong is also a medium for transmitting Balinese to the younger generation of Balinese so that this performing art contributes to ensuring the survival of the Balinese language. In today's digital era, efforts to maintain the Balinese language through the performing arts of drama gongs in the form of TV shows and digital media Youtube need to be continuously developed.